Hubungan antara Kesadaran Diri dan Kedisiplinan Belajar: Studi Korelasi pada Siswa Kelas V SD - Sitti Jauhar; Abd. Kadir. A; A. Rizky Nur Adha (Universtas Negeri Makassar, 2023)
This research uses a quantitative correlational study with the ex-post facto method which aims to determine the description of self-awareness, learning discipline, and the relationship between self-awareness and learning discipline of fifth grade students of SD Inpres 12/79 Jeppe'e. The population in this study were all students of class V, totaling 46 students using the saturated sample. The data analysis technique is descriptive and inferential statistical analysis. Based on the results of descriptive statistical analysis showed that the self-awareness of class V students can be categorized as good with a total percentage of 72%, student learning discipline can also be categorized as good with a total percentage of 74%. Then, the results of inferential analysis using the Pearson product moment correlation formula obtained rcount of 0.480 which can be categorized as having a moderate level of correlation. Meanwhile, the result of = 3.6295 > = 1.68023 so that the H0 is rejected and H1 is accepted. From the results of the study, it can be concluded that there is a significant relationship between self-awareness and learning discipline of fifth grade students at SD Inpres 12/79 Jeppe'e, Tanete Riattang Barat District, Bone Regency.